2000
DOI: 10.1063/1.1308530
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of metal surface in enhanced transmission through subwavelength apertures

Abstract: In order to understand the details of the extraordinary enhancement of the optical transmission through subwavelength holes in metal films, we have fabricated perforated free-standing metal films where the nature of the bulk and surfaces can be controlled independently. We find that the transmission enhancement depends only on the dielectric properties of the metal within a skin depth of the two in-plane surfaces and not on those of the film core, nor on the metal constituting the hole walls. This provides dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
172
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 251 publications
(177 citation statements)
references
References 19 publications
5
172
0
Order By: Relevance
“…It is a direct manifestation of the constructive or destructive wave interference over a certain path length and can lead to multiple transmission peaks as a function of frequency for wave transmission through impedance-mismatched layers. There is a renewed interest in electromagnetic FP resonances, especially their relevance to the recently observed transmission enhancement through subwavelength openings in normally opaque objects, [1][2][3][4][5][6][7][8] as well as to the ensuing debate on the relative contributions of surface wave versus diffraction in such phenomena. [9][10][11][12][13][14][15][16][17][18][19] It has been shown that light transmission through hole arrays in perfect-conductor thin films, where there can be no true surface waves, may be attributed ͑via Babinet's principle͒ to the reflection by the complementary structure consisting of planar arrays of perfect-conductor disks.…”
Section: Introductionmentioning
confidence: 99%
“…It is a direct manifestation of the constructive or destructive wave interference over a certain path length and can lead to multiple transmission peaks as a function of frequency for wave transmission through impedance-mismatched layers. There is a renewed interest in electromagnetic FP resonances, especially their relevance to the recently observed transmission enhancement through subwavelength openings in normally opaque objects, [1][2][3][4][5][6][7][8] as well as to the ensuing debate on the relative contributions of surface wave versus diffraction in such phenomena. [9][10][11][12][13][14][15][16][17][18][19] It has been shown that light transmission through hole arrays in perfect-conductor thin films, where there can be no true surface waves, may be attributed ͑via Babinet's principle͒ to the reflection by the complementary structure consisting of planar arrays of perfect-conductor disks.…”
Section: Introductionmentioning
confidence: 99%
“…As defined in the standard diffraction theory by Bethe [1] in 1944, a circular aperture with a subwavelength diameter transmits EM waves rather poorly ϳ(d/ ), 4 in which exiting EM waves are fully diffracted in all directions. These two disadvantages of low transmission and diffraction are the main problems in controlling of light, especially for subwavelength scales.…”
Section: Introductionmentioning
confidence: 99%
“…A resonant interaction leads to an enhanced transmission at wavelengths determined by the corrugation period [3][4][5][6][7][8]. It is also possible to confine the transmitted beam with the use of the periodically corrugated metal surface with subwavelength apertures [9 -12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations